Makna Hari Sabat Dalam Keluaran 20:11 dan Implikasinya bagi Umat dan Gereja Masa Sekarang - Lindung Hasiholan Zega; Juli Santoso; Citraningsih Basongan (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2021)
The seventh day or the Sabbath still has the view and belief that the fourth law is the law of God which does not change and remains, because Allah has made it for humans since creation, and by sticking to that law they are classified as saved people. Meanwhile, the majority of Christians worship on Sundays, with the view that because Christ was risen on the first day, the